A joint chance-constrained data envelopment analysis model with random output data - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi (Operational Research)

A Dynamic Decision Support System for Sustainable Supplier Selection in Circular Economy - Alavi, Behrouz; Tavana, Madjid; Mina, Hassan (Sustainable Production and Consumption)

An integrated quality and resilience engineering framework in healthcare with Z-number data envelopment analysis - Tavana, Madjid; Nazari-Shirkouhi, Salman; Farzaneh Kholghabad, Hamidreza (Health Care Management Science)

An integrated fuzzy framework for analyzing barriers to the implementation of continuous improvement in manufacturing - Tavana, Madjid; Shaabani, Akram; Valaei, Naser (International Journal of Quality & Reliability Management)

A fuzzy maturity-based method for lean supply chain management assessment - Soares, Gabriela Pereira; Tortorella, Guilherme; Bouzon, Marina; Tavana, Madjid (International Journal of Lean Six Sigma)

A robust cross-efficiency data envelopment analysis model with undesirable outputs - Tavana, Madjid; Toloo, Mehdi; Aghayi, Nazila; Arabmaldar, Aliasghar (Expert Systems with Applications)

Four research pathways for understanding the role of smart technologies in accounting - Mancini, Daniela; Lombardi, Rosa; Tavana, Madjid (Meditari Accountancy Research)

A new non-radial directional distance model for data envelopment analysis problems with negative and flexible measures - Tavana, Madjid; Izadikhah, Mohammad; Toloo, Mehdi; Roostaee, Razieh (Omega)

The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object–word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomised picture order and was analysed in respect of correct, prompt, and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of 10 brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97 vs. 96%) as well as high reliability coefficients (Goodman–Kruskal's gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency ( p < 0.05) and high age ( p < 0.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age ( p < 0.05). Moreover, a small learning effect was observed across the two runs of the test ( p < 0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimised for the clinical use to map and monitor language functions in patients. However, individual familiarisation before the clinical use remains advisable, especially for subjects that are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patients with clinically apparent word finding difficulties.

Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency - Nettekoven, Charlotte; Pieczewski, Julia; Neuschmelting, Volker; Jonas, Kristina; Goldbrunner, Roland; Grefkes, Christian; Weiss Lucas, Carolin (Human Brain Mapping)
Abstract Repetitive TMS (rTMS) with a frequency of 5–10 Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right‐handed, healthy subjects (m = 8, median age: 29 yrs) were investigated in two sessions, separated by 2–5 days. In each session, 10, 30, and 50 Hz rTMS were applied over the left hemisphere in a randomized order during a picture naming task. Overall, 30 Hz rTMS evoked significantly more errors (20 ± 12%) compared to 50 Hz (12 ± 8%; p <.01), whereas error rates were comparable between 30/50 and 10 Hz (18 ± 11%). Across all conditions, a significantly higher error rate was found in Session 1 (19 ± 13%) compared to Session 2 (13 ± 7%, p <.05). The error rate was poorly reliable between sessions for 10 (intraclass correlation coefficient, ICC = .315) and 30 Hz (ICC = .427), whereas 50 Hz showed a moderate reliability (ICC = .597). Spatial reliability of language errors was low to moderate with a tendency toward increased reliability for higher frequencies, for example, within frontal regions. Compared to 10 Hz, both, 30 and 50 Hz were rated as less painful. Taken together, our data favor the use of rTMS‐protocols employing higher frequencies for evoking language errors reliably and with reduced discomfort, depending on the region of interest.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Digitale Stille. Über die Bedeutung von Universitäten und Wissenschaft in der Covid-19-Pandemie - Flath, Beate (Das HEFT. Das Paderborner Veranstaltungs- und Kulturmagazin)

Data-Based Co-Creation and Participation: Reflections on an Ambivalent Relation by the Example of Music Apps - Flath, Beate (Pop – Power – Positions. Globale Beziehungen und populäre Musik (~Vibes – The IASPM D-A-CH Series 1)

Das Besondere und das Allgemeine in musikdidaktischen Kontexten. - Klingmann, Heinrich (Musikalische Bildung. Didaktik - Lehrerinnen- und Lehrerbildung - Theorie. Festschrift für Werner Jank.)

Doing Popkultur. - Klingmann, Heinrich; Ahlers, Michael (Musik-Didaktik. Praxishandbuch für die Sekundarstufe 1 und 2)

Textsortengeschichte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Das „geheime Europa“. Hugo von Hofmannsthals späte Parallelaktion zu Stefan Georges „geheimem Deutschland“ (1919–1923) - Heise, Tillmann („Sehnsucht nach dem Leben“. Tradition und Innovation im Werk Hugo von Hofmannsthals)

Das ‚Erfundene Gespräch‘ als transatlantischer Dialog. Gattungsvariationen und Gedankenexperimente in Hofmannsthals Gesprächsfragment "Brief ans Dial" (1925) - Heise, Tillmann (Hofmannsthal-Jahrbuch)

Verfreundete Europäer im Kampf mit der Moderne - Heise, Tillmann; Beßlich, Barbara (Ruperto Carola Forschungsmagazin)

A mathematical programming approach for equitable COVID-19 vaccine distribution in developing countries - Tavana, Madjid; Govindan, Kannan; Nasr, Arash Khalili; Heidary, Mohammad Saeed; Mina, Hassan (Annals of Operations Research)

Kriterien der Sanktionierung einer Verletzung der Bonitätsprüfungspflicht - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

Zum Anscheinsbeweis bei der Verwendung von Zahlungskarten mit PIN und zur Pflicht zur Sperranzeige. Anmerkung zu OLG Bremen, Beschl. v. 19.05.2021 - 1 W 4/21 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Ärger vor der Registereintragung - Bartlitz, David (Juristische Arbeitsblätter (JA))

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Melina Mercouri "Ich bin Griechin" (Είμαι Ρωμιά) - Janus, Richard (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Musik als Lebensmittel - Janus, Richard; Keuchen, Marion (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Themenpredigt: Reformation mit Beuys feiern - Janus, Richard (Reformation mit Joseph Beuys feiern. 31. Oktober 2021)

Reformation mit Joseph Beuys feiern. 31. Oktober 2021

Zeichen der Gemeinschaft und Begegnung. Göttliche Dreieinigkeit in der Orthodoxie - Janus, Richard

Dritte Internationale Summer School: "Formation of Faith and Trust" - Janus, Richard

Beeinflussung der Fließeigenschaften von Lasersinterpulver mittels Fließhilfsmitteln - Man, Yunhao

Wärmebehandlung von Polymeren zum Modifizieren von Materialeigenschaften für das Selektive Lasersintern - Seuthe, Jan

Fließfähigkeit von Schüttgütern bei erhöhten Temperaturen (Studienarbeit) - Ewe, Frederik

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

Tire Wear Reduction Based on an Extended Multibody Rear Axle Model - Schütte, Jan; Sextro, Walter (Vehicles)
To analyze the influence of suspension kinematics on tire wear, detailed simulation models are required. In this study, a non-linear, flexible multibody model of a rear axle system is built up in the simulation software MSC Adams/View. The physical model comprises the suspension kinematics, compliance, and dynamics as well as the non-linear behavior of the tire using the FTire model. FTire is chosen because it has a separate tire tread model to compute the contact pressure and friction force distribution in the tire contact patch. To build up the simulation model, a large amount of data is needed. Bushings, spring, and damper characteristics are modeled based on measurements. For the structural components (e.g., control arms), reverse engineering techniques are used. The components are 3D-scanned, reworked, and included as a modal reduced finite element (FE)-model using component mode synthesis by Craig–Bampton. Finally, the suspension model is validated by comparing the simulated kinematic and compliance characteristics to experimental results. To investigate the interaction of suspension kinematics and tire wear, straight line driving events, such as acceleration, driving with constant velocity, and deceleration, are simulated with different setups of wheel suspension kinematics. The influence of the setups on the resulting friction work between tire and road is examined, and an exemplarily calculation of tire wear based on a validated FTire tire model is carried out. The results demonstrate, on the one hand, that the chosen concept of elasto-kinematic axle leads to a relatively good match with experimental results and, on the other hand, that there are significant possibilities to reduce tire wear by adjusting the suspension kinematics.

Jubilate (08.05.2022): 1. Mose 1,1-4a.26-28.31a; 2, 1-4a - Janus, Richard (Er ist unser Friede. Lesepredigten 1. Advent 2021 bis Pfingstmontag 2022. Textreihe IV/1)

"Durch die Synästhesie wird deutlich, dass..." Die Wirklung sprachlicher Mittel in Gedichten erklären - Risse, Sylvia; Scholle, Oliver (Praxis Deutsch)

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th on Knowledge Capture Conference)

Autoethnografie und Kreatives Schreiben - Vochatzer, Stefanie; Engelmann , Sebastian (Journal der Schreibwissenschaft)

How to tell machines what to do. Wissenschaftler(innen)biografien in einem Padlet darstellen - Bauer, Maike; Hohwiller, Peter (Der fremdsprachliche Unterricht Englisch)

Diaspora-Literatures in the EFL Classroom – A new Didactic Impulse? - Bauer, Maike